A guide to assessing endoplasmic reticulum homeostasis and stress in mammalian systems. (11th November 2019) - Sicari, Daria; Delaunay‐Moisan, Agnès; Combettes, Laurent; Chevet, Eric; Igbaria, Aeid
Abstract : The endoplasmic reticulum (ER) is a multifunctional organelle that constitutes the entry into the secretory pathway. The ER contributes to the maintenance of cellular calcium homeostasis, lipid synthesis and productive secretory, and transmembrane protein folding. Physiological, chemical, and pathological factors that compromise ER homeostasis lead to endoplasmic reticulum stress (ER stress). To cope with this situation, cells activate an adaptive signaling pathway termed the unfolded protein response (UPR) that aims at restoring ER homeostasis. The UPR is transduced through post‐translational, translational, post‐transcriptional, and transcriptional mechanisms initiated by three ER‐resident sensors, inositol‐requiring protein 1α, activating transcription factor 6α, and PRKR‐like endoplasmic reticulum kinase. Determining the in and out of ER homeostasis control and UPR activation still represents a challenge for the community. Hence, standardized criteria and methodologies need to be proposed for monitoring ER homeostasis and ER stress in different model systems. Here, we summarize the pathways that are activated during ER stress and provide approaches aimed at assess ER homeostasis and stress in vitro and in vivo mammalian systems that can be used by researchers to plan and interpret experiments. We recommend the use of multiple assays to verify ER stress because no individual assay is guaranteed to be the most appropriate one. Abstract : The endoplasmic reticulum (ER) maintains cellular calcium homeostasis, lipid synthesis and productive secretory and transmembrane protein folding. Physiological, chemical and pathological factors that compromise ER homeostasis lead to endoplasmic reticulum stress (ER stress). A key challenge is to determine when ER stress starts and whether ER signaling pathways resolve it. However, ER researchers lack standardized criteria and methodologies for measuring ER stress. Here, we propose an ER tool box to help researchers to plan and interpret their experiments.